EDUKASI PEMANFAATAN TEKNOLOGI DIGITAL UNTUK MENAMBAH UANG SAKU SISWA SMKN 16 JAKARTA PUSAT - Didin Hikmah Perkasa; Magito Magito; Setiyo Purwanto; Nur Vitriani; Nur Endah Retno Wuryandari (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
This dynamic and continuously developing era in all aspects of life has caused many social changes. One of them is technological developments which make people very dependent on technology, especially after the emergence of the internet. The purpose of this article is to provide knowledge and understanding of how communication and technology can be used effectively and efficiently. Undoubtedly, many students use their cell phones to access the internet for various needs. This is also felt by students at SMKN 16 Central Jakarta, where most students have smartphones and often use social media for various purposes. So, we will teach usage